Competence of Cow Manure as a Sustainable Feedstock for Bioenergy and Biofertilizer Production - Ramesh Babu Aremanda; Semere Debretsion; Samuel Tesfalem; Robiel Menghisteab (Food, Agriculture and Natural Resources - NETWORKS, 2023)
Livestock development sector remained conspicuous in many developed and developing countries. Nevertheless, animal manure management became an increasing concern relative to environmental and economic constraints. The daily cow manure varies between 60-85 kg per 1000 kg of body biomass. Thus, 33 to 70 % of biomass could be recovered in the form of cow dung for value added products such as bioenergy and biofertilizer. Halhale dairy farm of Eritrea has a potential to produce approximately 25 tonnes of fresh cow manure per day. Proximate analysis of Halhale dairy manure (HDM) revealed that it contains a mean value of 14.35% of total solids, which inherently composed of 64.8% of Volatile solids and 23.3% of ash content. Detailed elemental analysis using X-ray fluorescent showed that it has 43.1% of C, 0.31% of S, 0.21% of P and 1.18% of K. Hydrogen and nitrogen contents of 4.57% and 1.58% were evaluated for HDM. Thermophysical parameters such as PH, SG and lower heating value(LHV) estimated as 7.025, 1.68 and 19.97 MJ kg-1 respectively. Significant LHV values indicate the aptness of HDM for fuel substitute. In addition, estimated C/N values of 25.68-27.3, ensure their best suitability for the biogas generation. Rich organic matter and high moisture content in HDM support large number of earthworms in vermicomposting. HDM have showed excellent N:P2O5 of 3.84 to favor the growth of any crop. Higher Si content of 4.32% along with desired micronutrients of 0.043% of Zn, <0.02% of Cu and 241 ppm of Mn, were measured for HDM samples. The effect of sodicity on soil measured in terms of sodium absorption rate (SAR), and a mean value of 0.84 was estimated for HDM.